Size of investment, opportunity choice and human resources in new venture growth - Thakur, Sanjay Prasad (Journal of Business Venturing, 1999)
A diversity of factors encompass entrepreneurship phenomena. An overview of theory and research in the field shows that entrepreneurship covers (1) number of start-up firms, (2) growth of the firm, (3) growth of the industrial economy, (4) individual mobility, and (5) social transformation. This paper tries to advance, through a partially developed formal model, an integration of some of the important aspects of entrepreneurship. Based on nearly 50 case studies carried out in the course of field work over North India, it examines the interplay of resources, opportunities and capabilities in new venture growth. The findings suggest that resource access may itself limit the range of opportunity choice and growth potential. Within these limits, managerial capability, as related to human resources in particular, could be more significant than hitherto recognized. A preliminary effort is made to develop a typology of firms based on the varying proportion of factors influencing growth of a venture. Further, a model of entrepreneurial firm stabilization and human resources is outlined. A path-based typology of new venture growth and human resource management is described. These include the use of family labor or supervisory resources, an empathetic leadership style and the presence of entrepreneurial teams. The findings in this paper result from a project to document profiles of entrepreneurs who have emerged through interactions with support systems, including entrepreneurship and small business development training programs in India. The states were divided into categories based on per-capita income and level of industrial development or backwardness. A judicious mix of purposive and random selection of cases was used. Criterion for selection included “extent of break from the past,” that is, non-business social origin of the entrepreneur and high-growth rate of the firm. Locationally, cases in a particular state have been selected from a) major urban center, b) smaller, more interior center, and c) small, remote center. The argument for small new ventures in developing countries lies in their positive employment and income generating effects. The claim rests on the presumed better efficiency of factor use in small enterprises—(surplus) labor in particular. Since the 1970s and the 1980s in the developed countries, too, new firms are acknowledged as being vital to an economy. The outlook for an individual new firm, however, can vary. High rates of sickness and mortality are also widely reported. Small firm start-ups are thought to play a role in widening the entrepreneurial base of a given society. It is an important expression of social mobility, as well as structural change, in a developing country context. At the micro-enterprise level, limited resources can restrict choice of opportunity to low growth ones. These represent a bad business idea, subsidized by family resources, including labor—the true self-employment cases. There could be a middle `growth zone’ where higher investment size widens opportunity choice. This slab represents the seedbed for firms with high-growth potential and merits the focus of policy makers, promotional agencies and advisory services. The strategic behavior of these firms can provide valuable insights into how `sweat equity’ is generated in growth ventures. There is a significantly sharp decrease in the number of firms in the third or highest, investment slab, approaching medium size. At this level, the size of the margin money required from the potential entrepreneur would limit the number of new entrants and their catchment sources. From a social transformation point of view, this may not be the desirable outcome. In the absence of developed markets for venture capital, this would render weak, the case for complete withdrawal of countervailing state assistance in industrially backward or depressed regions, which would favor those already advantaged.